Os dez anos do Jornal de Políticas Educacionais - Souza, Ângelo Ricardo de; Bruel, Ana Lorena; Ferraz, Marcos Alexandre dos Santos (Jornal de Políticas Educacionais, 2017)
Os dez anos do Jornal de Políticas Educacionais